2019
DOI: 10.1039/c8ra10251a
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced effects in the inorganic halide perovskite CsGeI3

Abstract: Perovskite photovoltaic materials are gaining significant attention due to their excellent photovoltaic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…The strain‐dependent structural changes were compared with the reported results for halide materials with the selected examples of M  X bond lengths as seen in Figure 4d. [ 36,43–47 ] The clear dependence of the bond length on the applied strain is very apparent by demonstrating the reduced bond lengths with the compressive strain. The reported differences in the bond length are based on the theoretical simulations incorporating the higher compressive or tensile strain values up to ≈10%.…”
Section: Resultsmentioning
confidence: 99%
“…The strain‐dependent structural changes were compared with the reported results for halide materials with the selected examples of M  X bond lengths as seen in Figure 4d. [ 36,43–47 ] The clear dependence of the bond length on the applied strain is very apparent by demonstrating the reduced bond lengths with the compressive strain. The reported differences in the bond length are based on the theoretical simulations incorporating the higher compressive or tensile strain values up to ≈10%.…”
Section: Resultsmentioning
confidence: 99%
“…From the literature it is evident that most of the halide perovskites follow similar band structure [27,28] and thus the descriptor model universalize the Eg variation under different types of strain. Also, in the context of uniform expansion or compression it has been shown that irrespective of the exchange-correlation (XC) functional, the variation of the bandgap with compression and expansion remains the same [13,[34][35][36]. The same is expected for the case of epitaxial strain.…”
Section: B Construction Of a Descriptor Modelmentioning
confidence: 88%
“…However, there are few studies on the photoelectric properties of CsGeI 3 under pressure. Although Liu et al studied some photoelectric properties of CsGeI 3 under hydrostatic pressure through first-principles, we still do not know enough about it [25]. Based on the first-principles, the change of photoelectric property of CsGeI 3 was explored at the hydrostatic pressure from −0.5 GPa to 0.5 GPa.…”
Section: Introductionmentioning
confidence: 99%